Intervensi Keperawatan untuk Penguatan Otot pada Anak Ensefalitis : Literature Review - Putri, Frischa Ananda; Cahya, Monica Dwi; Permaida, Permaida; Ciulianto, Rudy (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Encephalitis is an inflammatory condition of the brain parenchyma that often causes serious neurological disorders, as well as muscle weakness, motor dysfunction, impaired coordination, and decreased independence in children's daily activities. The broad clinical impact of encephalitis makes it not only an acute infection but also a condition with long-term implications for children's motor development and quality of life. Therefore, nursing interventions should focus on two main aspects: medical stabilization during the acute phase and structured rehabilitation during the recovery phase. This study aimed to evaluate the effectiveness of nursing interventions in improving muscle strength in children with encephalitis by reviewing the latest literature. This research employed a literature review approach, searching publications from 2020 to 2025 and identifying six articles that met the inclusion criteria. The analysis shows that 83.3% (n=5) of the articles focused on rehabilitative interventions such as muscle strengthening exercises, gait correction, balance exercises, range of motion (ROM), and functional activities, which have been shown to improve motor function and accelerate neurological adaptation. Meanwhile, 16.6% (n=1) of the articles emphasized the importance of close monitoring during the acute phase, focusing on neurological observation, complication prevention, maintaining respiratory stability, and monitoring the risk of increased intracranial pressure. These findings confirm that nursing interventions, which include comprehensive observation, family education, structured therapeutic measures, and multidisciplinary collaboration, significantly optimize neuroplasticity, improve postural control, and maximize muscle strength recovery. Overall, these evidence-based nursing interventions are crucial elements in enhancing the quality of life and independence of children with encephalitis.